Dental caries and salivary physiochemical characteristics among osteoporotic old adult women - Al-Sekab, Hiba F; Diab, Ban S (Journal of Baghdad College of Dentistry, 2014)
Background: Osteoporosis is a systemic skeletal disorder affects general health in addition to effect on salivary physical and chemical composition which lead to an adverse effect on oral health status. This study was conducted to evaluate the concentration of glycoprotein (osteonectin) in saliva and its effect on dental caries in relation to salivary flow rate and viscosity among osteoporotic women and compared to control group. Materials and Methods: The total sample composed of 60 females aged 60-65 years attending Al-Yarmook Teaching Hospital, 30 females diagnosed with osteoporosis by measuring bone density at the spine and femur with a dual-energy X-ray absorptiometry at T-score of >2.5, and 30 women without osteoporosis with T-score of Ë‚-1 (control group).The diagnosis and recording of dental caries was through the application of D1-4MFS index according to criteria of MÃ¼hlemman (1976). Stimulated salivary samples were collected under standardized condition, according to Tenovuo and LagerlÃ¶f, (1994). The flow rate and viscosity were estimated and then the saliva was analyzed for estimation of glycoprotein (osteonectin) by using Enzyme-linked immunosorbent assay (ELISA). Results: The percentage of dental caries occurrence was 100% among osteoporotic group and control group. Results revealed that DMFS value was higher but statistically not significant among osteoporotic women, Concerning DMFS components, the data of the present study showed that the DS was lower but statistically not significant among osteoporotic women, while MS value was significantly higher among them (t=2.044, P